Research progress on metal ion-induced Parkinson's disease - Jingying WANG; Binbin REN; Suna MA; Mengya GUAN; Yueyue YANG; Song WU (环境与职业医学, 2023)
Parkinson's disease (PD) is one of the hotspots in the research field of neurodegenerative diseases, and its pathogenesis is still controversial. Trace metal elements play an important role in normal growth and development of the human body. Metal ions can cross the blood-brain barrier and enter the brain, leading to α-synapnuclein aggregation, mitochondrial dysfunction, and degeneration of dopaminergic neurons, and then inducing the occurrence of PD. This article mainly reviewed the potential mechanisms of metal elements in PD, discussed the role of metabolic imbalance of common trace metals (copper, iron, manganese, and zinc) in PD, and put forward new insights into the treatment of PD.